Analysis of Factors Affecting on Development of Tourism Services Market - Bakaev Ziyovuddinkhon Toshbolta ugli (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2020)
In this article, in-depth analysis of problematic issues in the field of tourism services based on the factors influencing the development of the tourism services market. Therefore, paper has been searching for outcomes and shortcoming of the tourism development in the Republic of Uzbekistan. Finally, research has been pinpointed with related recommendations and suggestions as the whole.